Lung Adenocarcinoma in a Patient with Plasmacytoma - Atsunori Hiasa; Kazunori Nakase; Kazuo Fukutome; Hideki Nomura; Setsuko Ueno; Toshiro Mizuno; Naoyuki Katayama; Toshiaki Takeuchi (Case Reports in Hematology)
An increased risk of second malignancy is well recognized in patients treated for plasma cell neoplasms. However, second solid tumor is very rare in such patients. We report a case of a 68-year-old woman with plasmacytoma who developed lung adenocarcinoma.